Synchronization the Merdeka Curriculum at Madrasah 'Aliyah Learning Akidah Akhlak: Facing The Challenges of Moral Degradation in the Era of Society 5.0 - Achmadin, Balya Ziaulhaq; Haidar, Putri Bayu; Rifqi, Naflah Rifqi; Afwadzi, Benny (Journal of Research and Thought on Islamic Education (JRTIE), 2024)
This research aims to investigate the synchronization of the implementation of Merdeka Curriculum in Akidah Akhlak learning with the phenomenon of moral degradation that emerges in the era of Society 5.0. This research uses a qualitative approach with a case study as the research design. Data were collected through classroom observations, participatory interviews with teachers and students, and document analysis related to the curriculum and the phenomenon of moral degradation. The results showed that the implementation of Merdeka Curriculum in Akidah Akhlak learning has integrated moral values that are relevant to the context of the Society 5.0 era. However, the phenomenon of moral degradation that occurs around students is a challenge that needs to be overcome. The adaptation of the Merdeka Curriculum in Akidah Akhlak learning has integrated moral values that are relevant to the context of the Society 5.0 era. This is shown by the existence of, first, the first preventive stage of compulsory 'Ubbudiyah (Prayer, Reciting the Qur'an, Shalawat, Tahlil and character habituation), Second, the curative stage, disciplining students by the Code of Conduct team with dialogic interaction as a verbal mandate. Third, the rehabilitation stage, moral recovery to teachers, namely by acculturating 5S (Salam, Salim, Sapa, Polite, Santun), educating students to be critical and selective on information on the internet with the task of expressing opinions verbally about negative issues that are trending on the internet. In conclusion, efforts to synchronize the Merdeka Curriculum in Akidah Akhlak learning with the phenomenon of moral degradation in the Society 5.0 era require collaboration between schools, parents, and the community. By involving all parties, it is hoped that learning moral values can be more relevant and effective in facing the moral challenges faced by students in the Society 5.0 era.